2016
DOI: 10.1504/ijsmile.2016.077584
|View full text |Cite
|
Sign up to set email alerts
|

Social media adoption among university students: the role of gender, perceived usefulness and perceived ease of use

Abstract: Social media adoption has been phenomenal especially among the youth. This study seeks to examine the effect of perceived usefulness, perceived ease of use and gender on social media adoption. The survey research design was used in this study to provide a basis for the generalisation of the findings of this study. The respondents were mostly youth and were selected using convenience sampling technique. Data was analysed using multiple regression. The findings indicate that, perceived usefulness and perceived e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 25 publications
3
26
0
Order By: Relevance
“…Many other studies (e.g. Elkaseh et al, 2016;Dzandu et al, 2016;Kim and Sin, 2017;Sago, 2013;Shirazi, 2013;Sumida-Garcia and Costa-Silva, 2017) have found a significant relationship between PU and use of social media for various purposes. For instance, Sago (2013) found that the frequency of use of social media services is positively impacted by the level of perceived usefulness provided by social media services.…”
Section: Pu and Use Of Social Media For Political Participationmentioning
confidence: 90%
See 3 more Smart Citations
“…Many other studies (e.g. Elkaseh et al, 2016;Dzandu et al, 2016;Kim and Sin, 2017;Sago, 2013;Shirazi, 2013;Sumida-Garcia and Costa-Silva, 2017) have found a significant relationship between PU and use of social media for various purposes. For instance, Sago (2013) found that the frequency of use of social media services is positively impacted by the level of perceived usefulness provided by social media services.…”
Section: Pu and Use Of Social Media For Political Participationmentioning
confidence: 90%
“…The second section elicits data about the type of social media the students use for political participation, the type of political information the students use social media to share, the frequency of use of social media for political participation, the benefits derived from using social media for political participation, the challenges in using social media for political participation, as well as the influence of the four variables (PU, PEOU, SNs, and CSE) on USMPP. The items used to measure the variables were measured on four-point Likert scale ranging from Strongly Agree (4), Agree (3), Disagree (2), and Abdulrauf (2016), Compeau (1995), Dzandu et al (2016), Ezema et al (2015), Yang and DeHart (2016) and Venkatesh et al (2003). PU, PEOU, CSE and USMPP have 5 measurement items, while SNs has four.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The items used to measuring perceive enjoyment adopted from [57], [58], and [59]. The items measuring perceived usefulness, perceived ease of use and intention to use social media were adopted from [30], [60], and [61]. The items were measuring social influence adopted from [62], [63].…”
Section: Methodsmentioning
confidence: 99%